Assessment of cognitive dysfunction in kidney disease - Nasser, Mohamed El Tayeb; Shawky, Sahar; El Shahawy, Yasser; Sany, Dawlat (African Journal of Nephrology, 2010)
<p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Background: Cognitive dysfunction, include reducedmental alertness, intellectual impairment, decreasedattention and concentration, memory deficits anddiminished perceptual-motor coordination. Both CKDand chronic dialysis patients are thought to be associatedwith cognitive impairment. Cognitive impairment maydecrease an individual's quality of life, increase resourceutilization and result in suboptimal medical care.Neurophysiologic tests using imaging techniques areused to evaluate structural and functional abnormalities.Neuropsychological testing uses validated questions andscreening tests to evaluate cognition. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Setting and participants: This study was carried out on120 patients with different stages of CKD fromnephrology outpatient clinic and hemodialysis unit inAin Shams University Hospitals. Group I: 50 CKDpatients, stage ? and stage IV. Group II: 50 ESRDpatients on regular hemodialysis with K t/v > 1.1. GroupIII: 20 acute kidney injury patients, followed up till theirrenal functions stabilized. Group ?V: 20 healthy subjectsmatched with patients. All patients underwent laboratoryinvestigations and psychometric tests which include trialmaking test part B, digit span test, digit symbol test,mini-mental state examination. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Results: There were highly significant differences ofmean values of cognitive function tests between (groupsI,II and III as compared with group IV (control group),stage III CKD and stage IV CKD, CKD andhemodialysis patients, AKI patient at the insult and afterrecovery) and finally between hemoglobin and cognitivefunction tests score. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Conclusions: There were significant differences of cognitive function tests results between CKD, III,IV,V, AKI patients as compared with healthy group, suggesting that kidney disease affects cognitive performance, there were significant differences of cognitive function tests results between stage III CKD and stage IV CKD, suggesting that the degree of cognitive impairment is associated with the severity of CKD, also significant differences of cognitive function tests results between CKD and ESRD on hemodialysis, suggesting that dialysis improves cognitive performance. Our results showed significant differences of cognitive function tests results between AKI patients at the insult and after recovery, suggesting that AKI also impair cognitive function. Finally cognitive performance is affected by hemoglobin level in CKD stage III, IV, V on hemodialysis and AKI patients, suggesting that treatment of anemia in AKI, CKD and ESRD patients improve cognitive performance.